Pressure measurement of a bus model in wind tunnel for the improvement of the bus designs - Chin, Chung Han. (2013)
Based on existing bus designs, wind tunnel experiments are performed on different bus models in order to investigate their pressure distributions. In recent years, research works on improving bus designs were mainly performed through simulations (Computational Fluid Dynamics (CFD)) and little investigations were carried out in an actual wind tunnel. In this project, pressure distributions of different models are investigated in wind tunnel as wind tunnel experiment provides higher accuracy as compared to simulations. Pressure distribution measured provides detailed flow behavior and the results are then analyzed and compared in order to explore the possibility of modifying the shape of the bus for better fuel efficiency. The models studied are Mercedes-Benz O405, Scania K230 and Man NL 323 F.